A facile solvothermal growth of single crystal mixed halide perovskite CH3NH3Pb(Br1−xClx)31. Issue 37 (7th May 2015) - Zhang, Taiyang; Yang, Mengjin; Benson, Eric E.; Li, Zijian; van de Lagemaat, Jao; Luther, Joseph M.; Yan, Yanfa; Zhu, Kai; Zhao, Yixin
<x xml:space="preserve">Abstract</x> We demonstrate a facile solvothermal approach for growing mixed halide perovskite CH3NH3Pb(Br1−xClx)3 single crystals.